Weldability of A7075-T651 and AZ31B Dissimilar Alloys by MIG Welding Method Based on Welding Appearances - M., Ishak; M. Rafiqul, Islam (IOP Publishing, 2014)
It is not recommended to weld aluminium and magnesium dissimilar alloys using fusion welding method because of the formation of AlmMgn type intermetallic brittle compounds like Mg2Al3, Mg17Al12 etc. in the welding joint. These brittle compounds deteriorate the mechanical properties of the joint. But so far, insufficient researches have been attempted to stop the formation of AlmMgn type intermetallic brittle compounds in fusion welding method. The aim of this research work was to investigate on the weldability between A7075-T651 and AZ31B dissimilar alloys based on welding appearances and study the formation of intermetallic brittle compounds at the joint. In this research, A7075-T651 and AZ31B al¬loys were welded using ER5356 filler wire in MIG welding method in butt configuration. 100% argon was used as shielding gas. The results showed that, most of the welding appearances were moderate. The macroscopic investigation at all welding cross section showed that a lot of AlmMgn intermetallic brittle compounds were formed at the interface between weld seam and AZ31B parent metal side which caused macro cracks. A good number of macro pores were also observed at AZ31B parent metal side. These cracks and pores could easily cause the failure of the joint at very low stress